Leaf inoculation of Azospirillum brasilense and Trichoderma harzianum in hydroponic arugula improve productive components and plant nutrition and reduce leaf nitrate1 - Oliveira, Carlos Eduardo da Silva [UNESP]; Jalal, Arshad [UNESP]; Oliveira, Julia Revolti [UNESP]; Tamburi, Karen Vicentini [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (FapUNIFESP (SciELO), 2022)
Using beneficial fungi and bacteria to plant growth may reduce the leaf nitrate content and improve the quality of produced food. This study aimed to evaluate the isolated and combined effect of inoculation with Azospirillum brasilense and Trichoderma hazianum at two electrical conductivities on the nutrition and production of hydroponic arugula cultivation. The experiment was designed in randomized blocks, in a 4 x 2 factorial scheme, with five replications. The treatments consisted of inoculations (non-inoculated, A. brasilense, T. harzianum and co-inoculation) and two electrical conductivities (1.4 and 1.6 dS m-1). The isolated inoculation of T. harzianum and A. brasilense produced a higher root fresh mass, while the leaf chlorophyll index was higher with the inoculation of A. brasilense, concerning the other treatments. The inoculation of A. brasilense reduced the nitrate content in the arugula leaves. The inoculations and co-inoculation of A. brasilense and T. harzianum improved the yield components and plant nutrition, reduced the leaf nitrate content and promoted the biofortification of arugula leaves with Zn and Fe. In addition, the inoculation with T. harzianum increased the P and S leaf content.
Inoculação foliar de Azospirillum brasilense e Trichoderma harzianum em rúcula hidropônica melhoram os componentes produtivos e nutrição das plantas e reduzem o nitrato foliar
Keywords: Eruca sativa; growth-promoting microorganisms; nutrient film technique